119k views
4 votes
If y=6 when x=-3 find x when y= 24y varies directly with x

User Fargath
by
6.2k points

1 Answer

3 votes

Since y varies directly with x then


\begin{gathered} (y)/(x)=k \\ \text{Where k is the constant of proportionality} \end{gathered}

So,


\begin{gathered} (y)/(x)=(6)/(-3) \\ (y)/(x)=-2 \end{gathered}

Then, -2 is the constant of proportionality. So that,


\begin{gathered} (y)/(x)=-2 \\ (24)/(x)=-2 \\ \text{Solving for x you have} \\ (24)/(x)\cdot x=-2\cdot x \\ 24=-2x \\ (24)/(-2)=(-2x)/(-2) \\ -12=x \end{gathered}

Therefore, if y=6 when x=-3, then x=-12 when y=4.

User Caulfield
by
5.1k points